Legal Protection for Investors Againts Illegal Investment - Darmawan Wiridin; Zulfikar Putra; Nasrin; Ali Mustafa; Ansyar (Inovasi Pratama Internasional. Ltd, 2023)
This research was conducted with the aim of exploring the rise of fraudulent or illegal investments in Indonesia. The outbreak of fraudulent investment cases in the digital transformation era has harmed many people. There are various types of fraudulent investment modus operandi, including using Ponzi Schemes with cryptocurrency mode, using social media and influencers, and claiming to be an investment company that has been licensed by OJK. The research method used a literature study. The results show that the cause of people becoming victims of illegal investment fraud is not only because they are tempted by the large profits offered, but also the lack of knowledge of victims about the mechanism and workings of investment products. When investing, it should be in a place with clear legality. Investors invest in platforms that are licensed and supervised by regulators in the financial sector. Therefore, it is very important to verify and check the legality of the investment platform. In addition to socializing and educating the public regarding illegal investments, the Investment Alert Task Force also plays a role in preventing unlicensed business activities that have the potential to harm the public. The public is asked to be cautious of illegal investment offers. Investors must understand financial and digital literacy before investing because it is important to prevent investment fraud. Increased financial literacy will increase public knowledge of legal financial products.